Long-term outcomes and potential mechanisms of offspring exposed to intrauterine hyperglycemia - Yan, Yi-Shang; Feng, Chun; Yu, Dan-Qing; Tian, Shen; Zhou, Yin; Huang, Yi-Ting; Cai, Yi-Ting; Chen, Jian; Zhu, Miao-Miao; Jin, Min (Frontiers in Nutrition, 2023)
Diabetes mellitus during pregnancy, which can be classified into pregestational diabetes and gestational diabetes, has become much more prevalent worldwide. Maternal diabetes fosters an intrauterine abnormal environment for fetus, which not only influences pregnancy outcomes, but also leads to fetal anomaly and development of diseases in later life, such as metabolic and cardiovascular diseases, neuropsychiatric outcomes, reproduction malformation, and immune dysfunction. The underlying mechanisms are comprehensive and ambiguous, which mainly focus on microbiota, inflammation, reactive oxygen species, cell viability, and epigenetics. This review concluded with the influence of intrauterine hyperglycemia on fetal structure development and organ function on later life and outlined potential mechanisms that underpin the development of diseases in adulthood. Maternal diabetes leaves an effect that continues generations after generations through gametes, thus more attention should be paid to the prevention and treatment of diabetes to rescue the pathological attacks of maternal diabetes from the offspring.